2016
DOI: 10.5959/eimj.v8i3.454
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Burnout among Universiti Sains Malaysia Medical Students

Abstract: Introduction: The academic life of medical students can be considered as psychological toxic. About half of United States medical students experience burnout and more than 25% experience depression. This study aimed to determine the prevalence of burnout among medical students in a Malaysian medical school and its associated factors. Methods: This is a cross sectional study of 452 medical students from Universiti Sains Malaysia (USM). Copenhagen Burnout Inventory was distributed via Google Forms through Facebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
29
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 17 publications
7
29
6
Order By: Relevance
“…This was in agreement with the study done in Malaysia 2016, by Chin RWA et al where, a higher number of female medical students reported burnout (68.10%) than male medical students (67.7%). 27 These findings are comparable with a study that found approximately 50% of female and 33% of male medical students experiencedpsychological stress. 32 The female predominance of burnout may be because, women tend to feel emotionally exhausted, whereas, men feel more depersonalised.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This was in agreement with the study done in Malaysia 2016, by Chin RWA et al where, a higher number of female medical students reported burnout (68.10%) than male medical students (67.7%). 27 These findings are comparable with a study that found approximately 50% of female and 33% of male medical students experiencedpsychological stress. 32 The female predominance of burnout may be because, women tend to feel emotionally exhausted, whereas, men feel more depersonalised.…”
Section: Discussionsupporting
confidence: 86%
“…Personal burnout was the highest (81.6%), followed by work-related burnout (73.7%) and client-related burnout (68.6%). 27 The prevalence of burnout amongst medical students has been found to be comparatively high, between 45% and 71% of students affected in different studies. (22,(28)(29)(30) In the current study, work-related burnout(academic activities) higher than personal burnout this may be explained as burnout in those students is mainly due to the academic overburden more than the emotional exhaustion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Personal burnout refers to a degree of physical and psychological exhaustion experienced by an individual in home environment that includes ongoing health problem of loved ones, financial problem or relationship problem (Chin et al, 2016). This study revealed that 61.9% of nurses were experiencing personal burnout whereby similar finding was obtained from a study conducted in Australia which show that 57% of nurses experiencing personal burnout (Jordan et al, 2013).…”
Section: Discussionsupporting
confidence: 73%
“…The access to mental health support is paramount as growing data reveals poor mental health in clinical year students (37,38). The clinical education environment may potentially break the peer support where the students are fragmented in different clinical rotations (3).…”
Section: Theme 5: Supportmentioning
confidence: 99%